Cholecystectomy in a Patient with Hageman Trait - Girolami, A; Maffei, A; Brunetti, A; Lazzarin, M (Thrombosis and Haemostasis, 1970)
The case of a patient with Hageman trait who underwent cholecystectomy for cholelithiasis is reported. The surgical procedure was uneventful; no abnormal bleeding was noted during and after the operation. The transfusion of 4 cm3/kg b.w. of contacted 3-day old normal plasma corrected completely the coagulation abnormality. The glass and the silicone clotting times were slightly shortened even 64 h after the transfusion. The survival time for the infused factor XII activity resulted to be 41 h. 6 days after the plasma infusion the factor XII level was 1 % of normal. The significance of these findings is discussed.